Characterization of Spermatogonial Stem Cells Lacking Intercellular Bridges and Genetic Replacement of a Mutation in Spermatogonial Stem Cells - Iwamori, Naoki (Public Library of Science, 2012)
Stem cells have a potential of gene therapy for regenerative medicine. Among various stem cells, spermatogonial stem cells have a unique characteristic in which neighboring cells can be connected by intercellular bridges. However, the roles of intercellular bridges for stem cell self-renewal, differentiation, and proliferation remain to be elucidated. Here, we show not only the characteristics of testis-expressed gene 14 (TEX14) null spermatogonial stem cells lacking intercellular bridges but also a trial application of genetic correction of a mutation in spermatogonial stem cells as a model for future gene therapy. In TEX14 null testes, some genes important for undifferentiated spermatogonia as well as some differentiation-related genes were activated. TEX14 null spermatogonial stem cells, surprisingly, could form chain-like structures even though they do not form stable intercellular bridges. TEX14 null spermatogonial stem cells in culture possessed both characteristics of undifferentiated and differentiated spermatogonia. Long-term culture of TEX14 null spermatogonial stem cells could not be established likely secondary to up-regulation of CDK4 inhibitors and down-regulation of cyclin E. These results suggest that intercellular bridges are essential for both maintenance of spermatogonial stem cells and their proliferation. Lastly, a mutation in Tex14(+/−) spermatogonial stem cells was successfully replaced by homologous recombination in vitro. Our study provides a therapeutic potential of spermatogonial stem cells for reproductive medicine if they can be cultured long-term.